The Depiction of Loneliness Consciousness in Biancheng: 《边城》中对孤独意识的描绘 - Yi, Zhang; Xingli, Feng (Mandarinable: Journal of Chinese Studies, 2025)
In modern Chinese literature, Shen Congwen's representative work, Biancheng (Border City), is a very important work. This short story is inspired by Xiangxi and tells the emotional stories between several characters. It unfolds from the harmony between humans and nature, reflecting the loneliness of characters and the natural environment - not only from the author Shen himself, but also from his pursuit of idealized life forms and his display of the authenticity of life forms. So, how does Biancheng describe feelings of loneliness? What are the descriptions and characteristics of loneliness in Biancheng? What are the reasons behind describing loneliness? What is the writing value of depicting loneliness? This article will mainly use literature analysis method and comparative method, combined with concepts, theories, and methods in the field of thematic studies, to qualitative study these issues and attempt to provide a reasonable and feasible explanation. This study not only benefits the further development of Shen Congwen's research, but also inspires people to rethink the depiction of consciousness and its relationship with literary writing.